Posisi Pasar Ekspor Biji Kopi Indonesia Di Pasar Internasional: Pendekatan Almost Ideal Demand System (AIDS) - Adetya, Aulia; Rifin, Amzul; Nurmalina, Rita (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2025)
Indonesia is one of the main exporters of coffee commodities. Indonesia's coffee production is mostly exported abroad and the rest is to meet domestic needs. Indonesia's coffee exports cover five continents, namely Asia, Africa, Australia, the Americas, and Europe, with the main market share in Europe. This study aims to (1) analyze the market share of Indonesian coffee bean exports in the international market, and (2) analyze the market position of Indonesian coffee bean exports in the international market using the Almost Ideal Demand System (AIDS) approach. This study uses secondary data in the form of monthly time series for 12 years from 2010 to 2021 with HS code 0901111 (coffee, not roasted, not decaffeinated). The results show Indonesia's coffee bean export market share is third after Brazil and Colombia. Indonesia's price elasticity (uncompensa/1ted) is inelastic and has a negative relationship. The cross-price elasticity (compensated) between Indonesia and Brazil, Colombia, Guatemala, Ethiopia, and Uganda is negative and indicates a complementary and inelastic relationship. The expenditure elasticity of Indonesian coffee exports is negative, indicating that Indonesian coffee is included in inferior goods and is inelastic.